Burning for revenge - Marsden, John, 1950- (London : Quercus, 2013)
Having been separated from the New Zealand rescue troops they were guiding, five Australian teenagers continue their resistance against the unknown enemy invading their homeland.
Young Adult.
Young Adult
Keywords: Survival -- Fiction; War -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; War stories; Australia -- Fiction; Australia -- Fiction